ASSESSMENT OF PATIENTS’ KNOWLEDGE, ATTITUDE AND PRACTICE REGARDING DIABETES MELLITUS IN A TERTIARY CARE HOSPITAL IN EASTERN INDIA - DAS, ALAK KUMAR; GHOSH, DEBADRITA; GHOSH, JINIA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: Proper assessment and understanding of knowledge, attitude, and practice (KAP) among diabetic population towards this disease are important as diabetes needs lifelong adoption of healthy lifestyles for prevention and control. We aimed to evaluate the knowledge, attitude, and practice of diabetic patients regarding their disease in a tertiary care center. Methods: This was a questionnaire-based, cross-sectional study conducted on diabetic patients attending the diabetic clinic over 2 months. Administration of a pre designed, validated, and structured questionnaire consisting of 24 items was done by face-to-face interview. Results: Responses from 129 subjects were analyzed. Most of the subjects could not define diabetes (60.45%). However they identified the symptoms of diabetes (polyurea 62.79% and polyphagia 55.81%), and knew that lifestyle modification was necessary to control diabetes (exercise 66.66%, and dietary modification 62.79%). Majority had the notion that bitter substances could cure diabetes (51.93%) and insulin should be avoided (28.68%). Most of the subjects did not monitor blood glucose at home (81.4%) and did not take care of their feet (59.69%). Positive associations were found between patients’ knowledge and their family history, educational level, and duration of diabetes. Duration of diabetes and educational level were positively associated with practice of the patients. Conclusion: Present study reflects that diabetic patients require support and guidance for practicing better disease management. The role of a clinical pharmacist, as well as clinical activities such as patient counseling and pharmaceutical care program may aid in improving patients’ KAP of diabetes management.